ENCAPSULATION OF ZIDOVUDINE IN DIFFERENT CELLULOSIC ACRYLIC AND METHACRYLIC POLYMERS LOADED MICROSPHERES: IN VITRO CHARACTERIZATION AND COMPATIBILITY STUDIES - Mohima, Tania; Dewan, Irin; Islam, S. M Ashraful; Rana, Sohel; Hossain, Alamgir (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: The attempt of the present study was to improve bioavailability and dissolution rate along with reduction in dosing frequency of Zidovudine from microspheres. Methods: In this study an effort was taken to devise and evaluate Zidovudine sustained release microspheres using different polymers such as Ethyl cellulose (EC), Eudragit RS100, Hydroxypropyl methylcellulose (Methocel K4M and Methocel K15M) by emulsion solvent evaporation method. UV-Spectrophotometric method was applied to calculate the drug content and in vitro dissolution studied according to USP paddle method were carried out in Phosphate Buffer (pH 7.4) for 8 hours. Scanning electron microscopic (SEM) technique was performed to obtain the particle size and morphological changes due to different polymers. Drug polymer compatibility studies were performed by Fourier Transform Infrared (FTIR) spectroscopy, Differential Scanning Calorimetry (DSC) and X-ray Powder Difftactometry (XRD). Results: The maximum and minimum releases of microspheres were observed 93.12% and 75.07% respectively after 8 hours. Drug entrapment efficiency for formulations varied from 56.21% to 94.14%. The release kinetics were studied in different mathematical release models following the zero order, first order, Higuchi, Hixson-Crowel and korsemeyer to find out the linear relationship and release rate of drug. In this experiment, it is difficult to explain the exact mechanism of drug release. The drug might be released by both diffusion and erosion as the correlation coefficient (R2) best fitted with Korsemeyer model. No interaction between drug and polymers were observed from FTIR, DSC and XRD studies. Conclusion: In vitro study and different compatibility evaluation of Zidovudine from microspheres was showed that optimum release profiles may be obtained compared to pure drug.